2021
DOI: 10.1186/s12957-021-02319-x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte to C-reactive protein ratio predicts long-term outcomes for patients with lower rectal cancer

Abstract: Backgrounds The lymphocyte to C-reactive protein (CRP) ratio (LCR) is an indicator of systemic inflammation and host–tumor cell interactions. The aim of this study was to investigate the prognostic significance of LCR in lower rectal cancer patients who received preoperative chemo-radiotherapy (CRT). Methods Forty-eight patients with lower rectal cancer who underwent CRT followed by curative surgery were enrolled in this study. Routine blood examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…18 LCR could be an important predictive biomarker for the prognosis of patients with lower rectal cancer who undergo chemoradiotherapy followed by curative surgery. 19 Fan and Z et al showed that pretreatment of the C-reactive proteinlymphocyte ratio could be considered a feasible biomarker for the prognostic prediction of PC. 20 Tumor-infiltrating lymphocytes (TILs) are critical markers of the anti-tumor immune response, and positive associations have been described between the abundance of TILs and the favorable of patients with various cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 LCR could be an important predictive biomarker for the prognosis of patients with lower rectal cancer who undergo chemoradiotherapy followed by curative surgery. 19 Fan and Z et al showed that pretreatment of the C-reactive proteinlymphocyte ratio could be considered a feasible biomarker for the prognostic prediction of PC. 20 Tumor-infiltrating lymphocytes (TILs) are critical markers of the anti-tumor immune response, and positive associations have been described between the abundance of TILs and the favorable of patients with various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…18 LCR could be an important predictive biomarker for the prognosis of patients with lower rectal cancer who undergo chemo-radiotherapy followed by curative surgery. 19 Fan and Z et al showed that pretreatment of the C-reactive protein-lymphocyte ratio could be considered a feasible biomarker for the prognostic prediction of PC. 20…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified an elevated pretreatment CRP level as a significant prognostic factor for poor OS and DFS, in line with our results. Recently, the low levels of the lymphocyte-CRP ratio found in rectal cancer patients before nCRT were considered an independent prognostic factor for both recurrence-free survival and OS [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have found that high LCR predicts a good prognosis in different tumors [15,16,17,18]. However, some other studies have a different opinion [19,20,21]. Whether LCR is a reliable prognostic in ammatory immune marker remains unclear.…”
Section: Introductionmentioning
confidence: 99%